La toiture en remploi : charpente et couvertures de la cathédrale Saint-Pierre de Lisieux - Sylvain Aumard; Frédéric Épaud (Archéologie Médiévale)
Prior to the restoration of the Saint-Pierre Cathedral’s roofs in Lisieux, a study has been conducted on the ambulatory’s timber frame, as well as an estimation of the archaeological potential of the building’s roofing material. Having been studied before, the pieces that top the large attic date from the late 12th century and the early 13th century, constituting one of the best-preserved sets of that time period. Sampling and dendrochronological dating have shown that the ambulatory’s frame structure has been entirely rebuilt in 1763 using wood from previous timber frames, including the original one, dated from 1218 and composed of mono trusses and purlins. The other reuses show two other alterations of the ambulatory roofs: first in 1380, then in 1437-1442. Furthermore, the systematic study of the roofing material revealed that the roofs of the nave and of the northern aisle of the transept were still constituted of thousands of medieval tiles. The tiles, devoid of hooks, are for the larger part solely equipped with large perforations as well as a glazed gauge. Their chronological dating is yet to be established, but the late 12th century and the early 13th century are strongly considered periods. Along with the timber frames, they would currently form one of the best-preserved archaeological examples of medieval roofing materials in their architectural context.